Spring Accumulation Rates in North Atlantic Phytoplankton Communities Linked to Alterations in the Balance Between Division and Loss - Mojica, Kristina D. A.; Behrenfeld, Michael J.; Clay, Megan; Brussaard, Corina P. D. (Frontiers in Microbiology, 2021)
For nearly a century, phytoplankton spring blooms have largely been explained in the context of abiotic factors regulating cellular division rates (e.g., mixed-layer light levels). However, the accumulation of new phytoplankton biomass represents a mismatch between phytoplankton division and mortality rates. The balance between division and loss, therefore, has important implications for marine food webs and biogeochemical cycles. A large fraction of phytoplankton mortality is due to the combination of microzooplankton grazing and viral lysis, however, broad scale simultaneous measurements of these mortality processes are scarce. We applied the modified dilution assay along a West-to-East diagonal transect in the North Atlantic during spring. Our results demonstrate positive accumulation rates with losses dominated by microzooplankton grazing. Considering the dynamic light environment phytoplankton experience in the mixed surface layer, particularly in the spring, we tested the potential for incubation light conditions to affect observed rates. Incubations acted as short-term ‘light’ perturbations experiments, in which deeply mixed communities are exposed to elevated light levels. These “light perturbations” increased phytoplankton division rates and resulted in proportional changes in phytoplankton biomass while having no significant effect on mortality rates. These results provide experimental evidence for the Disturbance-Recovery Hypothesis, supporting the tenet that biomass accumulation rates co-vary with the specific rate of change in division.